In vitro seed propagation constraints of Mexican lady’s slipper orchid, Pichouaxtle, Cypripedium irapeanum - Moreno-Camarena, Mauricio (2025)
Cypripedium irapeanum known in Mexico as "Pichohuaxtle" in Nahuatl, is the most emblematic Mexican lady’s slipper orchid and one of the most studied cypripedioid species in Mesoamerica. Despite its protected status in Mexico, habitat loss driven by land-use change has severely reduced its populations. Ex situ conservation approaches are urgently needed to safeguard its genetic diversity, yet seed germination in the genus remains challenging due to innate dormancy and specific nutritional requirements. We collected seeds from two Mexican ecosystems where this species is distributed —Quercus and Tropical Dry Forests— and isolated mycorrhizal fungi from adult plants to examine both symbiotic and asymbiotic cultures. We found limitations in seed production due to flower ripening, ineffective pollination, or parasitism. Furthermore, germination was achieved after a cold treatment, and the best medium to obtain seedlings in vitro was Norstog medium. Two mycorrhizal fungi, isolated from adult plants belonging to the family Tulasnellaceae, formed a clade with previous isolates from American slipper orchids. One of these isolates promoted germination but later produced fungal incompatibility in vitro. Our study contributes to clarify previously undescribed processes in the biology of this highly appreciated and vulnerable species, supporting future efforts to propagate it from seed and obtain successful cultures.